Environmental-friendly indigenous biomass as solid acid catalyst for biodiesel production from palm oil: A comparative study - Mohd Khairul Amri, Kamarudin; Roslan, Umar; Azizah, Endut; Fathurrahman, Lananan (2016)
This study investigates the potential of three types of biomass namely oil palm frond, coconut shell and groundnut to be developed as green solid acid catalyst for biodiesel production. The carbon-based catalyst was prepared by the sulfonation of incompletely carbonized biomass using concentrated sulfuric acid. The porosity of prepared catalyst was characterized by adsorption/desorption technique and surface acidity was evaluated by means of back titration method. Coconut shell showed highest acid density of 0.51 mmol/g followed by groundnut shell and oil palm frond with 0.16 mmol/g and 0.12 mmol/g respectively. The biodiesel production was carried out at reaction conditions of methanol-to-oil ratio 20:1, reaction temperature 60 oC, reaction time 6 h and catalyst loading 6 wtyo. The highest biodiesel conversion was achieved using coconut shell as catalyst with 86.5 %, followed by groundnut shell and oil palm frond. The application of biomass derived solid acid catalyst explores new market value for waste material and further reduces cost and energy consumption in biodiesel production.